Optimization of transportation problem using solver and production profit with interior point algorithm (case study at Jenang Menara Kudus) - Rike Maulida (Unnes Journal of Mathematics, 2023)
Optimization of transportation problems and production profits is a goal to be achieved in this research. For the transportation problem, that is minimizing the cost of distributing goods from the place of origin to the destination with the help of the Solver program application, while for the production problem, that is maximizing profits with the Interior Point Algorithm with the help of the Matlab program application. Data collection was carried out by means of observation and direct interviews with the managers of the Menara Kudus Jenang Factory. In this study there were 8 types of processed Jenang Menara Kudus, namely Jenang Exclusive, Jenang Red Combination, Jenang Combination Black, Jenang Combination 500 gr, Jenang Large Mica Packaging, Jenang Small Mica Packaging, Jenang Refill 1 kg, Jenang Refill 0.5 kg. Observational data processed in this research are transportation cost data for each destination city, production capacity, production demand, raw material inventory, production composition, and production profit for each package. The results obtained in the optimization of transportation problems assisted by the Solver program to minimize transportation costs amounted to Rp. 1,433,500.00 while the transportation costs incurred by the Menara Kudus Jenang Factory before using the Solver program were Rp. 1,492,000.00. The calculation difference is IDR 58,500.00. The composition of the amount of each type of processed Jenang Menara Kudus is 800 packages of Jenang Exclusive, 600 packages of Jenang Combination Red, 460 packages Jenang Combination Black, 908 packages Jenang Combination 50 gr, 1000 packages Jenang Large Mika Packaging, 2540 packages Jenang Small Mika Packaging, 1,300 packages of 1 kg Jenang Refill, and 960 packages of 0.5 kg Jenang Refill, with the remaining raw materials being 38 kg of glutinous rice flour, 0 kg of palm sugar, 22 kg of granulated sugar, and 52 coconuts. Calculations in optimizing profits for Jenang Menara Kudus with the Interior Point Algorithm assisted by the application of the Matlab program amounted to Rp. 18,512,000.00 and calculations for maximizing profits carried out by the Jenang Menara Kudus Factory amounted to Rp. 18,420,000.00. So that it can be seen the difference before and after using the Matlab-assisted Interior Point Algorithm of IDR 92,000.00..